UJI KEMAMPUAN NaOH UNTUK RECOVERY KROMIUM(III) DARI LIMBAH CAIR PENYAMAKAN KULIT DENGAN METODE PENGENDAPAN - Hastutiningrum, Sri (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2006)
Waste from leather tanning process represents one the pollutants coming from va-rious existing industries. One of the dangerous compounds that contains in the liquid waste of leather tanning is chromium (III). In this study, the chromium (III) recovery from leather tanning liquid uses precipitation method.In general, the recovery of chromium (III) procedure starts with measurement of ini-tial pH, filtration of liquid waste and precipitation of chromium (III) using NaOH. The ad-dition of NaOH was also intended to increase the pH of the liquid waste. The liquid waste solution was then aged for several hours at various pH to obtain optimum conditions of precipitation. The obtained precipitation was filtered using various paper filters and finally dissolved again in sulfuric acid until the pH of the solution reached 2,0 – 2,8. The so-lution was analyzed for its chromium (III) content to determine the effectiveness of the recovery. Results of the study showed that Whatman 40 paper filter is more appropriate fil-ter for separating chromium (III) precipitate. The precipitation of chromium (III) proceeded effectively in the solution pH of 8, while the effective time of aging was found to be 24 ho-urs. Resolution of the chromium (III) precipitation using sulfuric acid reached its maximum level when sulfuric acid of 2,5 M was used. This study proved that liquid waste of chro-mium (III) from leather tanning may be reused as additive materials in the leather tanning processes after being recovered from the liquid waste using precipitation method.